Performance of primary care health professionals in the face of violence against women during the Covid-19 pandemic (Research, Society and Development, 2022)
The present study aimed to analyze the scientific literature on the performance of health care professionals primary focus on violence against women during the Covid-19 pandemic. This is an integrative review of the literature, carried out through a search in the Virtual Health Library and in the databases LILACS, SciELO and MEDLINE using two combinations of Descriptors: Gender-Based Violence AND health professionals AND Covid-19; the second combination was: Violence Against Women OR Gender-Based Violence AND Health Personnel OR Health Personnel AND Covid-19. Initially, twenty-four publications. After selection, based on the inclusion criteria and the objective of this work, six articles and submitted to semantic content analysis. In view of this, social isolation, as a measure of protection against the coronavirus, creates an ideal scenario for the situation of violence to be amplified and for many victims to have difficulty in denouncing the aggressor. The growth of violence has major repercussions in different aspects for women and their children. In this sense, the health professional plays an important role in the reception and in the identification of these victims. First-line support includes empathetic and nonjudgmental listening, asking about of needs and concerns, validate experiences and feelings, promote reassurance and refer them to support services. Thus, it is necessary to train health professionals to care for women in situation of violence, aiming at comprehensive care.